Gulliver's travels - Swift, Jonathan, 1667-1745 ([Boston, Mass] : Thomson Heinle, 2007)
The voyages of an Englishman carry him to such strange places as Lilliput, where people are six inches tall; Brobdingnag, a land of giants; an island of sorcerers; and a country ruled by horses
Title from container
Keywords: Voyages, Imaginary -- Early works to 1800; Voyages, Imaginary -- Fiction; Travelers -- Fiction; Gulliver, Lemuel (Fictitious character) -- Fiction